PENGARUH MODEL SIKAP TIGA KOMPONEN TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK BUDS ORGANICS - Ratu Chaterine Fajri; Anas Khair Prikurnia; Maulina Agustina (Politeknik Negeri Semarang, 2022)
Parents often choose products without harmful chemicals, synthetic perfumes, and dyes to protect their child's skin. Buds skincare is 95% organic, free of chemicals and artificial perfumes, and eco-certified. This study aims to determine how cognitive, emotional, and conative factors affect the sale of Organic Buds. This study includes all Buds Organics customers with more than three purchases. This study uses non-probability purposive sampling. According to the researcher's criteria, respondents must have used Tunas Organic products and bought them at least three times. In this study, samples were taken of 96 respondents who had used Organic Tunas products at least three times. The data analysis of this study evaluates the hypothesis. This research uses PLS software. The relationship between the conative and attitude components more strongly influences consumers' purchasing choices, according to this study. Attitudes affect purchase choice by 60.8%, so that customers who know the benefits of organic buds and want to buy them again are more likely to buy them.